A Case Study on Watershed Study for Flood Mitigation of Belgavi Region, Karnataka, India using ArcGIS - George, Geena; Bhavyashree, M. (AMC Indian Journal of Civil Engineering, 2022)
During the monsoon season, many regions in India are prone to floods among which Belagavi district, Karnataka (the study area) is one of the most affected. It has suffered huge lives and property losses. This study focuses on areas of rainfall analysis, watershed area mapping, flood vulnerable areas mapping and possible mitigation measures. DEM analysis is used to understand flood risk assessment. The rainfall data is collected for three taluks which are more prone to flood. These are Athani, Chikodi, and Raibagh in Belgavi regions. The study area was analyzed by generating maps for soil type, lithology, geomorphology, land use, and land cover using ArcGIS software. Maps were obtained for the percentage of land contributing to each attribute. Further flood vulnerability mapping has to be done by creating weightage map considering factors such as drainage density, soil type, precipitation, land use land cover, slope, and watershed compressed together by weighted overlay analysis, and the flood hazard zone map is developed to classify the areas into zones according to the risk of flooding which helps to suggest various non-structural mitigation measures.